RI 6854 Mass And Infrared Spectra Of Selected Unsaturated Hydrocarbons And Oxygenates - R. F. Kendall (The National Institute for Occupational Safety and Health (NIOSH), 1966)
Only a limited number of mass and infrared reference spectra of high purity unsaturated hydrocarbons and oxygenates are presently available in the literature. To aid Bureau of Mines research programs requiring such references, 64 mass spectra and 70 infrared spectra were obtained and are reported. The individual compounds, acquired from commercial sources, were purified by preparatory gas chromatography. Purity determinations were made using a combination of analytical gas chromatography, microhydrogenation, and catalytic deoxygenation. These spectra will aid spectroscopists in the identification of compounds of the types reported.